Does higher education matter for health? - Sisi Ji; Zheyi Zhu (Cardiff University, Cardiff Business School, 2022)
Using 6 sweeps from 1958 British NCDS data we adopt a quasi-parametric approach of propensity score matching to estimate causal effects of higher education attainment on a wide range of cohorts' health-related outcomes at ages 33, 42 and 50. The non-pecuniary benefits to HE attainments on health are substantial. Higher educated cohorts are more likely to report better health, maintain a healthy weight, be non-smokers and to have a higher sense of control on drinking alcohol and are less likely to be obese. We also highlight the importance of investigating incremental returns to HE within the lifetime of cohorts. Effects on self-reported health (SRH), BMI, drinking alcohol increase with age but continuously decrease with smoking frequency. When taking into account gender heterogeneity, HE has a larger effect on BMI and likelihood of being obese for males and a greater effect on SRH and drinking alcohol and smoking frequencies for females. Furthermore, we find no significant evidence that HE reduces the likelihood of depression, both for males and females.
Keywords: C21; I12; I23; I26; 330; Casual effect; Health; Higher Education; Propensity Score matching